External quality assurance in higher education: Nigeria and South Africa - Okafor, Theresa Udumaga (2015)
What is quality assurance? What is the purpose of higher education and how does it affect the way quality assurance is carried out? What value can be placed on quality assurance and could it enhance a student’s learning outcome?